Examining The Effects Of Service Quality And Brand Image On Customer Loyalty: A Study Through The Lens Of Customer Satisfaction - Lindayani, Lindayani; Napia, Raisa Nai (Jurnal Inovasi Bisnis dan Kewirausahaan, 2023)
This study aims to investigate the impact of service quality and brand image on customer loyalty mediated by customer satisfaction. The research incorporates both direct and indirect effects, considering various independent and dependent variables. The targeted population comprises customers who consistently repurchase Haus products. A purposive sampling approach was employed, resulting in a sample size of 96 respondents who received questionnaires. The collected data underwent analysis using SPSS software for validity and reliability testing. Subsequently, SmartPLS software was utilized for further data analysis. The primary objectives of this research are to ascertain the influence of service quality on customer satisfaction, the impact of brand image on customer satisfaction, the relationship between customer satisfaction and customer loyalty, the effect of service quality on customer loyalty mediated by customer satisfaction, and finally, the influence of brand image on customer loyalty mediated by customer satisfaction. The findings reveal that service quality significantly impacts customer satisfaction by 20.3%, while brand image exerts a substantial influence at 75.1%. Moreover, customer satisfaction is a significant driver of customer loyalty, accounting for 89.7%. The study also identifies a notable impact of service quality on customer loyalty through customer satisfaction (18.2%), and brand image similarly affects customer loyalty through customer satisfaction by 67.3%.